2019
DOI: 10.3390/ma12111855
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Vegetation Growing Recycled Concrete and Synergistic Effect with Plant Roots

Abstract: Vegetation growing recycled concrete (VGRC) is a relatively new building material that has both biocompatibility and engineering function. The basic performance of VGRC was investigated by experimental analysis, and the hydration products and pore structure of different VGRC mix proportions were studied by X-ray diffraction (XRD), scanning electron microscope (SEM), and industrial computed tomography (CT). The results show that ultrafine slag can reduce Ca(OH)2 content in cementing material and has a filling e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In recent years, vegetation lightweight porous concrete (VLPC) has emerged as an innovative integration of traditional concrete technology with the advantages of horticulture [ 1 , 2 ]. VLPC boasts a considerable pore volume and a distinctive pore structure [ 3 , 4 , 5 , 6 ], resulting in enhanced water permeability [ 7 ], efficient heat dissipation capacity [ 8 ], and notable sound absorption capability [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, vegetation lightweight porous concrete (VLPC) has emerged as an innovative integration of traditional concrete technology with the advantages of horticulture [ 1 , 2 ]. VLPC boasts a considerable pore volume and a distinctive pore structure [ 3 , 4 , 5 , 6 ], resulting in enhanced water permeability [ 7 ], efficient heat dissipation capacity [ 8 ], and notable sound absorption capability [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The greater the porosity of the planting concrete, the more space there is for plant growth and the better the plants will grow; however, higher porosity leads to lower strength for concrete [ 6 ]. The type, shape, and size of the coarse aggregates and the water–cement ratio are influencing factors that greatly affect the physical and mechanical properties of the planting concrete, such as porosity and strength [ 7 , 8 ]. Kim et al [ 9 ] replaced the natural coarse aggregate with blast furnace slag, and when the blast furnace slag aggregate was replaced from 0 to 100%, the porosity of the planting concrete increased from 15 to 27.5%.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the compressive strength decreased from 13 MPa to 11.5 MPa. Furthermore, using recycled aggregates as a substitute for natural aggregates with the same aggregate gradation of 5–25 mm [ 7 ], it was found that the compressive strength of the planting concrete decreased by 32%. Compared to natural aggregates, recycled aggregates have undergone mechanical wear and chemical degradation over a longer period of time, and mechanical damage from the crushing process causes more microcracks in the aggregates, resulting in their poorer performance as concrete aggregates; another reason for poor performance is the presence of mortar and interface transition zones in recycled concrete aggregates [ 10 ], which leads to weaker bonding between recycled aggregates and cement [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete’s raw materials, which include river sand and gravel, are mainly excavated from the riverbed and its surrounding area. However, the exploitation of river sand and gravels has caused serious damage to the river’s ecological environment [2,3,4,5]. For these reasons, most governments have determined to restrict the related exploitation engineering, so there is a shortage of concrete materials and its price has risen [6].…”
Section: Introductionmentioning
confidence: 99%